PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 004 BELILAS KECAMATAN SIBERIDA - ', Kasnidah; Kurniaman, Otang; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was motivated by the facts that occurred in the SDN 004 Belilas Kecamatan Siberida still low absorption of third-grade students in materials science lessons. The problem of this research is "Does the implementation of cooperative learning model STAD can improve learning outcomes IPA third grade students of SDN 004 Belilas Kecamatan Siberida?". The purpose of this research to improve learning outcomes IPA Grade III SDN 004 Belilas Siberida District of Indragiri Hulu through cooperative learning model STAD. This study took place in Class III SDN 004 Belilas Kecamatan Siberida and held 11 April to 27 April 2016 with a number of subjects as many as 20 people composed of nine female students and 11 male students. This research is a classroom action research conducted in two cycles. Based on the results obtained percentage of classical completeness individual and by implementing cooperative learning model STAD, before action is completed by 20%, in the first cycle increased by 55% and the second cycle increased by 90%. Improved learning outcomes in basic score a 64 increase to 76.75 in the first cycle, with improvement 19.92%. In the second cycle the average student learning outcomes return increased to 84.5 with improvement that occurred from the first cycle to the second cycle is 10.1%. From the results of these actions can be concluded that the application of cooperative learning model Student Team Achievement Division (STAD) can increase the value of learning outcomes IPA third grade SDN 004 Belilas Kecamatan Siberida. Keywords: Model STAD Cooperative Learning, Learning Outcomes, IPA